Peculiar speech : preaching to the baptized - Willimon, William H. (W.B. Eerdmans Pub. Co, 1992)
Because the baptized people in a congregation are called peculiar, the preacher needs to address them with "peculiar speech", letting the Biblical text call them to live a transformed life in keeping with the baptism. Includes three powerful baptismal sermons.